Risk assessment in waste sampling activity for a selected food industry / Nurul Syazreen Razali - Nurul Syazreen , Razali (2020)
Waste sampling is one of the main activities during environmental audit. This activity has been estimated as a non-risky activity and lead to inadequate risk assessment in the activity. The purpose of this study is to create a safer workplace for enforcement body in general and DOE officer in specific during waste sampling activity. Main objectives are to identify the hazards, further assess the hazards and determine the control measure to reduce the hazards. Observation and on-the-job training have been conducted to three food industry located in Shah Alam to identify the hazards. Structured surveys were conducted with 293 participants to further identify hazards among DOE officers. Risk assessment and risk control have been tabulated in HIRARC form after hazards identification process. The study showed that there were potential concerns in chemical, physical, biological and ergonomic hazards in waste sampling activity during environmental audit. The analysis from survey showed that the officers were aware of the hazards exposed but lack of implementation in risk control. Most of the respondents agreed that risk control could eliminate or reduced the hazards exposure. From HIRARC form, there were 3 high risk hazards from the total of 43 hazards identified which needed immediate action in order to eliminate or reduced the risk. Risk control has been suggested in this study including the involvement of premises to provide a safer waste sampling point. It can be concluded that there are significant hazards in waste sampling activity although most of them are at low and medium risks. Without proper action taken by the employer and officer, these hazards can be a threat to life and property damage.